Persepsi Petani Kakao di Kabupaten Jembrana Terhadap Koperasi Kerta Semaya Samaniya - Ni Kadek Ayu Wiratini; Made Ary Meitriana (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
The purpose of this study was to determine the perception of cocoa farmers in Jembrana Regency towards the Kerta Semaya Samaniya Cooperative. The type of this research is descriptive research, to describe the perception of cocoa farmers in Jembrana Regency towards the Kerta Semaya Samaniya Cooperative. This study uses all cocoa farmers in Jembrana Regency who are not yet members of the cooperative as the population with 99 cocoa farmers as samples used in this study after calculating the sample size using the Slovin formula. To collect data from 99 respondents used an instrument in the form of a questionnaire and then analyzed using descriptive analysis to obtain research results that can later be used in answering the research problem formulation. The results showed that the perception of cocoa farmers in terms of the expectation dimension obtained a score of 3,269, so it could be categorized as agree. The perception of cocoa farmers in terms of the dimension of need obtained a score of 1.825, so it can be categorized as strongly agree. The perception of cocoa farmers in terms of the dimension of need obtained a score of 2,777, so it was categorized as agree.